Is the WTO Passé? - Bagwell, Kyle; Bown, Chad P.; Staiger, Robert W. (Journal of Economic Literature, 2016)
The WTO has delivered policy outcomes that are very different from those likely to emerge out of the recent wave of preferential trade agreements (PTAs). Should economists see this as an efficient institutional hand-off, where the WTO has carried trade liberalization as far as it can manage, and is now passing the baton to PTAs to finish the job? We survey a growing economics literature on international trade agreements and argue on this basis that the WTO is not passé. Rather, and subject to some caveats, our survey of research to date suggests that the WTO warrants strong support while a more cautious view of PTAs seems appropriate. (JEL F13, F14, K33, N70)